The effect of gamma radiation on structure of struvite-К - Bereznyak, E.P.; Dikiy, N.P.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Sayenko, S.Y.; Uvarov, V.L.; Fedorets, I.D.; Hodyreva, Y.S. (Вопросы атомной науки и техники, 2017)
The effect of gamma radiation upon functional characteristics of nanostructural struvite-K is analyzed. Spectra of absorption struvite-K have been measured in infra-red area. Results of a microstructure of samples after of a gamma irradiation to a dose 1.35·10⁵Gy are described. It has shown that after gamma irradiation the phase composition of the sample essentially does not change, and there is a crystallization of amorphous phosphate and the structural or-dering of struvite-K and magnesite occurs.